Anelastic relaxation due to interstitial solutes diffusion in Nb and Nb-1 wt% Zr - Florêncio, O.; Silva, P. S.; Grandini, Carlos Roberto [UNESP] (Trans Tech Publications, 2006)
Metals and alloys containing solute atoms dissolved interstitially often show anelastic behavior due to a process know as stress-induced ordering. The application of mechanical spectroscopy measurements to diffusion studies in body-centered cubic metals has been extensively used in the last decades. However the kind of preferential occupation of interstitial solutes in body-centered cubic metals is still controversial. The anelastic properties of the Nb and Nb-1 wt% Zr polycrystalline alloys were determined by internal friction and oscillation frequency measurements using a torsion pendulum inverted performed between 300K and 650K, operating in a frequency oscillation in the hertz bandwidth. The interstitial diffusion coefficients of oxygen and nitrogen in Nb and Nb-1 wt% Zr samples were determined at two distinct conditions: (a) for low concentration of oxygen and (b) for high concentration of oxygen.
Keywords: Internal friction; Interstitial diffusion; Nb; Nb-Zr alloys; Nitrogen; Oxygen; Anelastic behavior; Body-centered cubic metals; Stress-induced ordering; Bandwidth; Niobium compounds; Physical properties; Relaxation processes; Spectroscopic analysis; Diffusion in solids